Study of Cardiac Features in Adults with Down Syndrome - Condoluci, Claudia; Galli, Manuela; Cimolin, Veronica; Rigoldi, Chiara; Albertini, Giorgio (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Down Syndrome (DS) has a significant impact on the development of many tissues, most notably in the heart and in the brain. According to the clinical need to better investigate these aspects, the main aim of this study was to make an overview on the cardiac features in adult individuals with DS. The following data of 37 individuals with DS (range: 18-60 years) were collected and analysed: age, gender, height, weight, waist to height ratio (WHER), smoking history and cardiac parameters (heart rate and blood pressure), blood glucose level or glycaemia, cholesterol (total, high-density lipoprotein – HDL - and low-density lipoprotein - LDL - cholesterol) and triglycerides. In addition, their gait pattern were quantified with 3D Gait Analysis. BMI, WHER and cholesterol HDL results were above the upper limits of the recommended range in people with DS; on the contrary, blood pressure, heart rate, glycaemia, cholesterol-LDL and triglycerides were within the recommended range. Comparing males and females in the DS group, the females showed statistically different values for cholesterol-total, and triglycerides values, with lower values in comparison to males. In motor performance, people with DS presented abnormal gait patterns. Some significant correlations were found: age with LDL, WHER with weight and BMI, systolic with diastolic blood pressure, total cholesterol with LDL and triglycerides. Our results showed that adults with DS suffer from a high prevalence of physical disorders, including overweight and obesity, and abnormal cholesterol values, together with abnormal gait pattern.